The Danish Welfare State - Frederiksen, Morten. author. aut Link
VIII, 269 p.
Keywords: The Danish Welfare State analyzes a broad range of areas, such as globalization, labor marked, family life, health and social exclusion, the book demonstrates that life in a modern welfare state is changing rapidly, creating both challenges and possibilities for future management.